The effectiveness of botanical insect glue Surawung langit (Salvinia hyspanica) and mass controlling application technique on Empoasca in tea plant - Odih Sucherman; Sugeng Harianto; Sobar Darana (Jurnal Penelitian Teh dan Kina, 2016)
Empoasca (Empoasca flavescens) is a major pest of tea plant in almost all elevations and can lead of lost production more than 40%.  Chemical insecticide is still use to control this pest. In a long term, this  could be increase the cost as well as environmental damage. To support an environmentally sound control method, an experiment has been conducted by using active ingredient of surawung langit leaf extract and using of mass controlling tool. The experiment was carried out at a productive tea plant of two years prunning, clone GMB-7, block B4, Pasir Sarongge Experimental Garden, Cianjur.   The experiment was arranged in a factorial randomized block design with eight treatments, and replicated three times. The aim the experiment was to evaluate the effectiveness of botanical insect glue surawing langit (salvinia hyspanica) and mass controlling application technique on empoasca in tea plant. Result showed that botanical insect glue surawing langit at 10 and 20% applied using mass controlling tool with two blowers were effective in catching of Empoasca as swell as its attack intensity and shoot production.